Is it a match? a novel method of evaluating medical school success. Issue 1 (1st January 2018) - Chang, Leslie L.; Nagler, Alisa; Rudd, Mariah; Grochowski, Colleen O'Connor; Buckley, Edward G.; Chudgar, Saumil M.; Engle, Deborah L.
ABSTRACT: Background: Medical education program evaluation allows for curricular improvements to both Undergraduate (UME) and Graduate Medical Education (GME). UME programs are left with little more than match rates and self-report to evaluate success of graduates in The Match. Objective: This manuscript shares a novel method of program evaluation through a systematic assessment of Match outcomes. Design: Surveys were developed and distributed to Program Training Directors (PTDs) at our institution to classify residency programs into which our UME graduates matched using an ordinal response scale and open-ended responses. Outcomes-based measures for UME graduates were collected and analyzed. The relationship between PTD survey data and UME graduates' outcomes were explored. Open-ended response data were qualitatively analyzed using iterative cycles of coding and identifying themes. Results: The PTD survey response rate was 100%. 71% of our graduates matched to programs ranked as 'elite' (36%) or 'top' (35%) tier. The mean total number of 'Honors' grades achieved by UME graduates was 2.6. Data showed that graduates entering elite and top GME programs did not consistently earn Honors in their associated clerkships. A positive correlation was identified between USMLE Step 1 score, number of honors, and residency program rankings for a majority of the programs. Qualitative analysis identified research, faculty, and clinical exposure as necessary characteristics of 'elite' programs:. Factors considered by PTDs in the rating of programs included reputation, faculty, research, national presence and quality of graduates. Conclusions: This study describes a novel outcomes-based method of evaluating the success of UME programs. Results provided useful feedback about the quality of our UME program and its ability to produce graduates who match in highly-regarded GME programs. The findings from this study can benefit Clerkship Directors, Student Affairs and Curriculam Deans, and residency PTDs as they help students determine their competitiveness forspecialties and specific residency programs.